Jasmonate biochemical pathway - Liechti, Robin; Farmer, Edward E (Science's signal transduction knowledge environment (STKE), 2006)
Plants possess an interrelated family of potent fatty acid-derived regulators-the jasmonates. These compounds, which play roles in both defense and development, are derived from tri-unsaturated fatty acids [alpha-linolenic acid (18:3) or 7Z,10Z,13Z-hexadecatrienoic acid (16:3)]. The lipoxygenase-catalyzed addition of molecular oxygen to alpha-linolenic acid initiates jasmonate synthesis by providing a 13-hydroperoxide substrate for the formation of an unstable allene oxide that is then subject to enzyme-guided cyclization to produce 12-oxo-phytodienoic acid (OPDA). OPDA has several fates, including esterification into plastid lipids or transformation into the 12-carbon co-regulator jasmonic acid (JA). JA, the best-characterized member of the family, regulates both male and female fertility (depending on the plant species) and is an important mediator of defense gene expression. JA is itself a substrate for further diverse modifications. Genetic dissection of the pathway is revealing how the different jasmonates modulate different physiological processes. Each new family member that is discovered provides another key to understanding the fine control of gene expression in immune responses, in the initiation and maintenance of long-distance signal transfer in response to wounding, in the regulation of fertility, and in the turnover, inactivation, and sequestration of jasmonates, among other processes. The Jasmonate Biochemical Pathway provides an overview of the growing jasmonate family, and new members will be included in future versions of the Connections Map.